Companies with R&D abroad make Germany a strong research location - Heike Belitz (DIW Economic Bulletin, 2017)
In recent years, German companies have invested more in research and development (R&D) abroad. After a prolonged plateau period, the proportion of investment abroad rose to around 35 percent; concurrently R&D expenditure in Germany has continued to rise sharply. Growth abroad did not occur at the expense of domestic research. Foreign companies in Germany have also invested more in R&D recently but have not yet topped the 2011 record high. Measured by stocks of foreign direct investment, they should still have some potential for higher expenditure in R&D. In international comparison, the growth in private R&D investment in Germany in recent years was high. This was mainly driven by German companies with R&D abroad.
Keywords: D24; F21; L60; O31; 330; research and development; globalisation; multinational companies